KAREL JAROMIR ERBEN’S MYSTICAL BALLAD "THE WEDDING SHIRTS" IN ANTONIN DVOŘÁK’S ARTISTIC INTERPRETATION - Naumova , Olena (Collection of scientific papers «ΛΌГOΣ», 2024)
Czech musical culture has given the world many enduring artistic values, with traditions of original folk art and professional composition. Its flourishing in the XIX century, due to the rise of the national liberation movement, was clearly manifested not only in folk art, but also in the outstanding masterpieces of Czech composers who stood on the level of European achievements and strove to reveal the national uniqueness of Czech music. One such composer was Antonín Dvořák.